(untitled) (Jurnal Pelita Pendidikan, 2022)
This study aims to determine the knowledge and participation of biology education students and UIR mathematics education students regarding the use of plastic food wrap as a source of environmental pollution. The research was conducted in March-May 2021. The research method is a survey method. Data collection techniques using tests, questionnaires, interviews, and documentation. The instrument used is a test based on Bloom’s taxonomy with 15 questions and a questionnaire of 20 statements, instrument testing, and reliability testing. The population in this study amounted to 243 students and used a saturated sample. The results showed that the average knowledge of UIR biology and mathematics education students about the use of plastic food wrap as a source of environmental pollution was 70.36% in the good category. Meanwhile, the participation of UIR biology and mathematics education students regarding the use of plastic food wrap as a source of environmental pollution with a value of 84.57% in the very good category. It can be concluded that the knowledge and participation of UIR biology and mathematics education students regarding the use of plastic food wrap as a source of environmental pollution are in a good category